Working Memory Capacity and Language Processing Efficiency in EFL Learners - Raifa Naswa Khodijah; Widya Maharani; Shafira Hasan Hasibuan; Yani Lubis (Jurnal Pendidikan dan Sastra Inggris, 2024)
This study aims to explore how working memory capacity influences language processing efficiency among English as a Foreign Language (EFL) learners. Using a qualitative approach, data were collected through language processing tasks and semi-structured interviews that examined participants’ cognitive experiences while engaging with complex linguistic input. Interpretative Phenomenological Analysis (IPA) revealed several key patterns. Learners with higher working memory capacity were able to retain information longer, process complex sentences more efficiently, and employ strategies such as chunking and contextual prediction. In contrast, learners with lower capacity experienced higher cognitive load, frequent information loss, and reliance on linear processing that hindered their ability to construct global meaning. Subjective factors such as anxiety also influenced processing efficiency, particularly for those with lower capacity. These findings indicate that language processing efficiency is shaped by an interplay of cognitive resources, processing strategies, and subjective experiences. The pedagogical implications highlight the need for instructional approaches that account for cognitive differences, enabling instruction to be more responsive to learners’ individual needs.